Heavy goods vehicle: review of studies involving accident factors - Nor Izzah Zainuddin,; Rizati Hamidun,; Ahmad Kamil Arshad,; Wardati Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of heavy goods vehicles (HGV) has grown locally and globally. In this regard, every road user faces a high accident risk and is susceptible to traffic-related injuries and deaths. There is a substantial focus on law enforcement to prevent overloading, speeding, and illegal substance use among drivers. Nonetheless, evidence about the complex causes of HGV accidents is still scarce. Thus, this paper aims to outline the literature related to HGV study and examine factors of HGV accidents. Several factors that significantly contribute to accidents have been identified in the literature review. The study has established three main HGV accident factors with 15 sub-HGV accident factors. The Human Factor was the most dominant, while the Vehicle Factor was the least acclaimed HGV accident factor. The review also found several areas for further empirical improvements by including diverse data sources, a more extensive database, and more advanced data analysis. Moreover, technology advancements are required to capture more detailed and richer data for future studies on HGV. Future studies related to HGV accidents are essential in reducing the fatality rate in line with the Sustainable Development Goals (SDG) Goal 3 target 6, which reduces the number of individuals killed or wounded in vehicle accidents worldwide.